Sustainability of public finances in Finland and the four largest Euro-area Economies - Helvi Kinnunen; Pasi Kuoppamäki (Bank of Finland, 1998)
The paper analyses the sustainability of fiscal policy in the four largest countries of the EMU area and Finland with the aim of assessing whether current fiscal policies are compatible with the Stability and Growth Pact in the medium term.The sensitivity of the deficit and debt ratios to changes in the real interest rate and economic growth is also assessed.Moreover, since population ageing will cause an extra burden on public finances, the fiscal pressure of rising pension costs in the longer term is also investigated. The baseline calculations for the medium term suggest that fiscal policy is sustainable in all countries except perhaps France. However, highly indebted countries such as Italy are clearly more sensitive to changes in interest rates.The results indicate that there is little or no room for active fiscal policy.The room for manoeuvre is even more limited if one takes into account that tax rates most likely need to be lowered in many countries, especially in Finland and Italy, due to tax harmonization and tax competition. Moreover, population ageing will impose pressures on public finances in the long run.Only Finland and Italy seem to be in a position to cope with increasing pension expenditures over the long run.
URN:NBN:fi:bof-20140807625
Keywords: 330